2018
DOI: 10.1021/acs.est.8b00403
|View full text |Cite
|
Sign up to set email alerts
|

The Oxygenic Photogranule Process for Aeration-Free Wastewater Treatment

Abstract: This study presents the oxygenic photogranule (OPG) process, a light-driven process for wastewater treatment, developed based on photogranulation of filamentous cyanobacteria, nonphototrophic bacteria, and microalgae. Unlike other biogranular processes requiring airlift or upflow-based mixing, the OPG process was operated in stirred-tank reactors without aeration. Reactors were seeded with hydrostatically grown photogranules and operated in a sequencing-batch mode for five months to treat wastewater. The new r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(157 citation statements)
references
References 34 publications
5
151
1
Order By: Relevance
“…Previous studies recently reported microalgal enrichment under phototrophic conditions using activated sludge from wastewater treatment as inoculum. 22,23 Hence, it was not surprising to find out that the centrate herein used also contained microalgae.…”
Section: Nutrients Removalmentioning
confidence: 90%
“…Previous studies recently reported microalgal enrichment under phototrophic conditions using activated sludge from wastewater treatment as inoculum. 22,23 Hence, it was not surprising to find out that the centrate herein used also contained microalgae.…”
Section: Nutrients Removalmentioning
confidence: 90%
“…Microalgal-bacterial granules can be obtained under aerated conditions and non-aerated conditions in the presence of light, and are called activated algal granules and photo-granules, respectively (Abouhend et al, 2018;Tiron et al, 2017). During the formation of photo-granules, extracellular polymeric substances secreted by microalgae play a key role, with a higher ratio of polysaccharides to proteins .…”
Section: Microalgal-bacterial Granules Technologymentioning
confidence: 99%
“…The production of oxygen by these cyanobacteria via photosynthesis is typically coupled to the oxygen consumption of heterotrophic bacteria that convert organic matter, for example, from wastewater, into CO 2 , which is immediately used by cyanobacteria for biomass synthesis. This syntrophic relationship between bacteria makes photogranules a promising candidate biomass for wastewater treatment (Abouhend et al, 2018, 2020). External aeration in conventional activated sludge is currently the major energy expenditure of wastewater treatment plants (Longo et al, 2016; Shoener et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…External aeration in conventional activated sludge is currently the major energy expenditure of wastewater treatment plants (Longo et al, 2016; Shoener et al, 2014). In an OPG process, external aeration is not necessary (Abouhend et al, 2018) and therefore no energy for aeration is required. However, this energy may be off‐set in a bioprocess using OPGs by the energetic requirements of mixing and the potential supply of electric light for pollution removal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation